Formulating the Competence of the Future Computer Science Teacher in Programming and Prepare Them for Using of Digital Technologies - M. U. Ashurov; M. M. Ashurova (Researchparks Publishing, 2022)
This article deals with the formation of professional ICT competence of future teachers of computer science and in the study of programming. The technique of effective teaching of programming for the creation of electronic learning resources is presented. Several examples are given in C++, Python, and Delphi programming languages.